TAFSIR DAN HERMENEUTIKA ABDULLAH AHMED AN-NA’IM: REINTERPRETASI SYARIAH DALAM KONTEKS HAK ASASI MANUSIA DAN NEGARA SEKULER - Ismatul Latifah; Muhammad Irsyad Mu’afa; Andi Rosa (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2025)
This paper examines the interpretive thinking and hermeneutical approach of Abdullah Ahmed An-Na'im, a contemporary Islamic scholar from Sudan who is widely known as a figure of Islamic legal reform. The discussion focuses on analysing An-Na'im's contextual interpretation method in understanding Sharia law, human rights, and the relationship between religion and the state. Through a critical hermeneutical approach, An-Na'im seeks to reinterpret religious texts so that they remain in line with universal human values and the demands of modernity, without abandoning the normative roots of Islam. This research uses a qualitative method based on a literature study by examining An-Na'im's major works such as Toward an Islamic Reformation (1990) and Islam and the Secular State (2008). The results of the study show that An-Na'im's interpretation is contextual, ethical, and progressive, with an emphasis on moral hermeneutics oriented towards maqāṣid al-sharī‘ah as the basis of universal ethics. He rejects a rigid and textualistic approach to Islamic law and offers a new paradigm that integrates justice, human rights, and pluralism within the framework of a modern secular state.